Interleukin-28 Polymorphism: Ethnic variations and the response to chronic hepatitis C treatment in Malaysia - Chee-Hoong, Hoe; Mohd Suan, Mohd Azri; Chee-Hock, Hoe; Thean-Hock Tang, Tang; Kuang-Kiat, Kiew; Abu Hassan, Muhammad Radzi; Huan-Keat, Chan (2018)
We refer to the article by Merican, which provides a comprehensive overview of chronic hepatitis C (CHC) management. The author highlighted the concern over the exorbitant cost of direct-acting antivirals, which is the reason for their limited use in Malaysia currently. Based on the findings of the previous studies, the author also underlined that Asians receiving the conventional, interferon-based treatment generally have a higher sustained virological response (SVR) rate as compared with Caucasians and African Americans, mainly due to the interleukin-28B (IL28) single nucleotide polymorphism (SNP) across different ethnic populations. Nonetheless, to date, information on the variations in IL-28 genotypes among different ethnic groups in Malaysia is still limited.